Tyrosine-Protein Phosphatase Non-receptor Type 9 (PTPN9) Negatively Regulates the Paracrine Vasoprotective Activity of Bone-Marrow Derived Pro-angiogenic Cells: Impact on Vascular Degeneration in Oxygen-Induced Retinopathy - Desjarlais, Michel; Ruknudin, Pakiza; Wirth, Maëlle; Lahaie, Isabelle; Dabouz, Rabah; Rivera, José Carlos; Habelrih, Tiffany; Omri, Samy; Hardy, Pierre; Rivard, Alain; Chemtob, Sylvain (Frontiers in Cell and Developmental Biology, 2021)
Background & Aim. Insufficient post-ischemic neovascularization is an initial key step in the pathogenesis of Oxygen-Induced Retinopathy (OIR). During neovascularization, pro-angiogenic cells (PACs) are mobilized from the bone marrow and integrate into ischemic tissues to promote angiogenesis. However, the modulation of PAC paracrine activity during OIR and the specific mechanisms involved remain to be explored. Because PTPN9 is reported to be a negative regulator of stem cell differentiation and angiogenesis signaling, we investigated its effect on PAC activity in the context of OIR. Methods & Results. In a rat model of OIR, higher levels of PTPN9 in the retina and in bone marrow derived PACs are associated with retinal avascular areas, lower levels of the mobilization factor SDF-1 and decreased number of CD34+/CD117+/CD133+ PACs. PACs exposed ex-vivo to hyperoxia display increased PTPN9 expression, which is associated with impaired ability of PAC secretome to promote angiogenesis in vivo (choroidal vascular sprouting) and in vitro (endothelial cell tubule formation) compared to the secretome of PACs maintained in normoxia. Suppression of PTPN9 (using siRNA) increases VEGF and SDF- 1 expression to normalize PAC secretome during hyperoxia, leading to restored angiogenic ability of PAC secretome. Moreover, endothelial cells exposed to the secretome of siPTPN9-treated PACs expressed increased levels of activated form of VEGF receptor 2 (VEGFR2). In the rat model of OIR, intravitreal injection of secretome from siPTPN9-treated PACs significantly reduced retinal vaso-obliteration; this was associated with higher retinal levels of VEGF/SDF-1, and increased recruitment of PACs (CD34+ cells) to the retinal and choroidal vessels. Conclusions. Our results suggest that hyperoxia alters the paracrine proangiogenic activity of BM-PACs by inducing PTPN9, which can contribute to impair post-ischemic revascularization in the context of OIR. Targeting PTPN9 restores PAC angiogenic properties, and provide a new target for vessel integrity in ischemic retinopathies.